0320 Anthropometric Evaluation of Obstructive Sleep Apnea (OSA) in a Community Population. (12th April 2019) - Silva, Graciela E; Vana, Kimberly D; Quan, Stuart F; Rojo-Wissar, Darlynn M; Kobayashi, Ume; Haynes, Patricia L
Abstract: Introduction: Sole reliance on body mass index (BMI) as an indirect measure of obesity may lead to imprecise predictions of obstructive sleep apnea (OSA) risk. Adding an indirect measurement of fat distribution, such as neck circumference (NC), may be insufficient for improving sensitivity. A simple method without measuring blood pressure might be useful in remote locations. We compared anthropometric ratios to determine if they alone predicted the apnea hypopnea index (AHI) or could be replacement variables for the NC item in the alternative scoring of the STOP-Bang Questionnaire (SBQ). Methods: Eighty-six participants with anthropometric measurements from the ongoing Assessing Daily Activities Patterns through occupational Transitions (ADAPT) study were included. We evaluated the following ratios: neck-stature ratio (NSR), neck-wrist ratio (NWR), and the waist-stature ratio (WSR). Receiver operating characteristic (ROC) analyses evaluated each ratio's ability to predict AHI≥15 and AHI≥ 30. We further evaluated the SBQ's ability to predict AHI≥15 and AHI≥ 30 with each ratio subsequently replacing the NC item in the SBQ. Each ratio was dichotomized at the mean, with a score of 1 being greater than the mean in lieu of the NC item. Results: Mean age was 40.2 (40% male), and mean BMI was 30.2 kg/m 2 . The mean NCs were 40.2 cm for males and 35.1 cm for females. The ROCs for the NSR, NWR, WSR, and SBQ predicting AHI≥15 were 0.72, 0.71, 0.59, and 0.64, respectively (p=.22), and were 0.57, 0.57, 0.47, and 0.56, respectively (p=.017), predicting AHI≥ 30. When each ratio replaced NC in the SBQ, ROCs were 0.70, 0.69, 0.69, and 0.64, respectively (p=.45), predicting AHI≥15 and 0.51, 0.54, 0.49, and 0.55, respectively (p=.08), predicting AHI≥ 30. Conclusion: Anthropometric ratios that relate NC to body frame, NSR and NWR, performed similarly to the SBQ when predicting AHI ≥30. The simple alternative scoring with NSR and NWR replacing NC performed similarly in SBQ prediction. The NSR and NWR may have useful application in remote areas. Support (If Any): 1R01HL117995-01A1